2018
DOI: 10.1590/s0102-865020180110000006
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of transglutaminase-2 prevents early age-induced vascular changes in mice

Abstract: Purpose: To determine whether the absence of transglutaminase 2 enzyme (TG2) in TG2 knockout mice (TG2-/-) protect them against early age-related functional and histological arterial changes. Methods: Pulse wave velocity (PWV) was measured using non-invasive Doppler and mean arterial pressure (MAP) was measured in awake mice using tail-cuff system. Thoracic aortas were excised for evaluation of endothelial dependent vasodilation (EDV) by wire myography, as well as histological analyses. Results: PWV and MAP we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…45 Transglutaminase 2 activity is inhibited by the vasoprotective molecule nitric oxide, 46 and we have previously shown that exposure to TMAO reduces vascular nitric oxide bioavailability by stimulating ROS production. 13 Furthermore, genetic knockdown 47 or pharmacological inhibition 48 of transglutaminase 2 lowers BP and improves vascular endothelium-dependent dilation in old rodents, and, although the evidence is mixed, 47 may attenuate age-related increases in aortic stiffness. 49 Thus, although we were unable to assess transglutaminase activity due to limited availability of aortic lysate, this remains a potential mechanism of interest moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…45 Transglutaminase 2 activity is inhibited by the vasoprotective molecule nitric oxide, 46 and we have previously shown that exposure to TMAO reduces vascular nitric oxide bioavailability by stimulating ROS production. 13 Furthermore, genetic knockdown 47 or pharmacological inhibition 48 of transglutaminase 2 lowers BP and improves vascular endothelium-dependent dilation in old rodents, and, although the evidence is mixed, 47 may attenuate age-related increases in aortic stiffness. 49 Thus, although we were unable to assess transglutaminase activity due to limited availability of aortic lysate, this remains a potential mechanism of interest moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…The central role of TG2’s transamidation function in this diverse set of disease processes has resulted in a keen interest to develop selective and specific inhibitors that can be deployed in vivo to interrupt its transamidation reaction [ 17 19 ]. In the vasculature, TG2 inhibition or depletion protects against age-associated vascular stiffening [ 2 , 4 , 20 ] and delays resistance vessel remodeling induced by hypertensive and vasoconstrictive stimuli [ 21 23 ]. Thus, TG2’s transamidation function has an established role in vascular remodeling and stiffening.…”
Section: Introductionmentioning
confidence: 99%
“…Aging-associated fibrosis also occurs in other organs, including lungs ( Schafer et al, 2017 ; Sicard et al, 2018 ); the prevalence of chronic lung diseases and idiopathic pulmonary fibrosis in the elderly may reflect this occurrence ( Budinger et al, 2017 ). It has been previously reported that TG2 mediates cardiac ventricular ( Oh et al, 2017 ) and systemic arterial ( Armstrong et al, 2018 ) stiffness in rodent models of aging. Similar to that of the obesity/metabolic syndrome, it has been proposed that the aging process may be under the regulation of enhanced glycolysis with reduced mitochondrial function ( James et al, 2015 ; Feng et al, 2016 ; Cho et al, 2017 ; Jang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%